NORWEGIAN SCABIES IN AIDS PATIENT: A CASE REPORT - Pratamasari, Meita Ardini; Agusni, Indropo; Prakoeswa, Cita Rosita Sigit; Astari, Linda; Sandhika, Willy (Institute of Topical Disease Universitas Airlangga, 2016)
Scabies is a skin infection caused by Sarcoptes scabiei var. hominis. This disease may present severe clinical manifestations in immune-compromised patient, well-known as Norwegian scabies or crusted scabies.A 36-year old man with AIDS had chief complaint thick crust almost all over his body in this case. History of household member infected by scabies before was present. Clinical findings show hyperpigmented macules unsharply marginated, covered with thick scales and accompanied by papules, fissures, and erotion. T cell CD4 level was 12 cell/Î¼L. Scraping examination showed scabies infection and so did the histopathology examination. This patient was treated by topical Permethrin 5% combined with 2-4 ointment application in between permethrin usage. Before topical scabicide was given, thick crust was previously treated by topical urea 10% and wet dressing by normal saline. On day 14 after the patient first came there was lesion improvement.